Chip-Scale Ultra-Low Field Atomic Magnetometer Based on Coherent Population Trapping - Hyun-Gue Hong; Sang Eon Park; Sang-Bum Lee; Myoung-Sun Heo; Jongcheol Park; Tae Hyun Kim; Hee Yeon Kim; Taeg Yong Kwon (Sensors, 2021)
We report a chip-scale atomic magnetometer based on coherent population trapping, which can operate near zero magnetic field. By exploiting the asymmetric population among magnetic sublevels in the hyperfine ground state of cesium, we observe that the resonance signal acquires sensitivity to magnetic field in spite of degeneracy. A dispersive signal for magnetic field discrimination is obtained near-zero-field as well as for finite fields (tens of micro-tesla) in a chip-scale device of 0.94 cm3 volume. This shows that it can be readily used in low magnetic field environments, which have been inaccessible so far in miniaturized atomic magnetometers based on coherent population trapping. The measured noise floor of 300 pT/Hz1/2 at the zero-field condition is comparable to that of the conventional finite-field measurement obtained under the same conditions. This work suggests a way to implement integrated atomic magnetometers with a wide operating range.